The Legal Implications of European Union Enlargement: A Ukranian Perspective - Buletsa, Sibilla (Maastricht 30: A Central European Perspective, 2025)
The acquisition of candidate status is highly valued by Ukrainian civil society, as it serves as a mechanism to build renewed momentum for reform. Over the past few months, the government and civil society have made a concentrated and successful effort to attain candidate status inside the European Union. From Kyiv’s perspective, it can be argued that the Eastern Partnership has effectively accomplished its initial goals. Ukraine’s willingness to embrace realignment or adopt new forms is contingent upon the attainment of demonstrable security benefits.Ukraine’s membership in the European Union (EU) offers several key advantages, including better trade prospects, ongoing implementation of reforms, and the opportunity for accelerated economic and social development. Ukraine’s membership in the European Union would allow the country to achieve a degree of development similar to that of prominent European nations and to solidify its position within a union of economically advanced and politically independent states. Empirical data from numerous countries demonstrates that joining the European Union (EU) will bring several benefits to both the general population and businesses.Keywords: enlargement, European union, Ukraine, agreement, reforms